Tuning Interface Bridging Between MoSe2 and Three-Dimensional Carbon Framework by Incorporation of MoC Intermediate to Boost Lithium Storage Capability - Chen, Jing; Luo, Yilin; Zhang, Wenchao; Qiao, Yun; Cao, Xinxin; Xie, Xuefang; Zhou, Haoshen; Pan, Anqiang; Liang, Shuquan (Nano-Micro Letters, 2020)
Highlights MoSe 2 /MoC/C multiphase boundaries boost ionic transfer kinetics. MoSe 2 (5–10 nm) with rich edge sites is uniformly coated in N-doped framework. The obtained MoSe 2 nanodots achieved ultralong cycle performance in LIBs and high capacity retention in full cell. Interface engineering has been widely explored to improve the electrochemical performances of composite electrodes, which governs the interface charge transfer, electron transportation, and structural stability. Herein, MoC is incorporated into MoSe 2 /C composite as an intermediate phase to alter the bridging between MoSe 2 - and nitrogen-doped three-dimensional (3D) carbon framework as MoSe 2 /MoC/N–C connection, which greatly improve the structural stability, electronic conductivity, and interfacial charge transfer. Moreover, the incorporation of MoC into the composites inhibits the overgrowth of MoSe 2 nanosheets on the 3D carbon framework, producing much smaller MoSe 2 nanodots. The obtained MoSe 2 nanodots with fewer layers, rich edge sites, and heteroatom doping ensure the good kinetics to promote pseudo-capacitance contributions. Employing as anode material for lithium-ion batteries, it shows ultralong cycle life (with 90% capacity retention after 5000 cycles at 2 A g −1 ) and excellent rate capability. Moreover, the constructed LiFePO 4 //MoSe 2 /MoC/N–C full cell exhibits over 86% capacity retention at 2 A g −1 after 300 cycles. The results demonstrate the effectiveness of the interface engineering by incorporation of MoC as interface bridging intermediate to boost the lithium storage capability, which can be extended as a potential general strategy for the interface engineering of composite materials.